Subtract the radicals: 4√18 - 5√32 - 2√12 - 18√3

### 1 Answer | Add Yours

The result of `4*sqrt 18 - 5*sqrt 32 - 2*sqrt 12 - 18*sqrt 3` has to be determined.

`4*sqrt 18 - 5*sqrt 32 - 2*sqrt 12 - 18*sqrt 3`

=> `4*3*sqrt 2 - 5*4*sqrt 2 - 2*2*sqrt 3 - 18*sqrt 3`

=> `12*sqrt 2 - 20*sqrt 2 - 4*sqrt 3 - 18*sqrt 3`

=> `-8*sqrt 2 - 22*sqrt 3`

**The result of `4*sqrt 18 - 5*sqrt 32 - 2*sqrt 12 - 18*sqrt 3` = `-8*sqrt 2 - 22*sqrt 3`**

### Join to answer this question

Join a community of thousands of dedicated teachers and students.

Join eNotes